Health geography in case of Zasavje: Linking of atmospheric air pollution and respiratory diseases data - Kukec, Andreja; Zaletel - Kragelj, Lijana; Farkaš - Lainščak, Jerneja; Eržen, Ivan; Herakovič, Andrej; Božnar, Marija Zlata; Mlakar, Primož; Grašič, Boštjan; Zadnik, Vesna (Acta geographica Slovenica, 2014)
The aim of the study was to assess the association between atmospheric air pollution and respiratory diseases in children on the level of small spatial units in the Zasavje. The health and environmental data were obtained for the period between January 1 and December 31, 2011. Studied small spatial units were designed on the basis of estimated level of atmospheric air pollution and digital maps and boundaries of local communities and settlements. The impact of atmospheric air pollution on respiratory diseases was analysed by using the Bayesian models. Considering the identified deficiencies, the presented methodolgy can often be used to identify areas with a higher health risks.